Chemical and Mineralogical Characterizations of Different Kaolinitic Clays from Burkina Faso: Feasibility for the Synthesis of Geopolymer Binders - Seick Omar Sore; Philbert Nshimiyimana; Adamah Messan; Elodie Prud’homme; François Tsobnang; Gilles Escadeillas (Geosciences, 2025)
Researchers are exploring eco-friendly alternatives to Portland cement, such as geopolymers, which require reactive aluminosilicate sources. This study evaluated the reactivity of six calcined clays (heated at 700 °C) in the presence of an alkaline solution. The calcined samples from kaolinite quarries in Kamboinsé, Kandarfa, Saaba, Sabcé, Selogo, and Tougou were subjected to chemical and mineralogical analyses. The results indicated a high aluminosilicate content (>50%), with kaolinite reaching up to 83.1%, and an amorphous fraction of up to 31.8%, a key factor influencing reactivity. Geopolymer pastes, prepared using a 12 M NaOH solution and each of these calcined clays, exhibited varying setting times: 24 h for the Saaba clay (the most reactive) compared with 48 h or even up to 7 days for the least reactive. The evaluation of the compressive strength of the geopolymer pastes revealed varying performances depending on the composition of clay. The Saaba clay showed the highest strength (14 MPa), attributed to its high kaolinite content (83.1%) and amorphous phase (31.8%), and thus reactivity. This was followed by Kamboinsé with 10.5 MPa (58.3% kaolinite; 24.3% amorphous phase), Selogo with 4.6 MPa (42.9%; 20.4%), Tougou with 1.4 MPa (44.1%; 20.4%), Kandarfa with only 0.7 MPa (31.3%; 19.2%), and Sabcé, which did not set with 0 MPa (24.1%; 13.7%). A discussion between the chemical and mineralogical compositions of the different clays and the mechanical characteristics of the synthesized pastes highlighted the importance of kaolinite content and its amorphous nature on the reactivity of the geopolymer binders. These findings highlight its potential for applications such as stabilized bricks or geopolymer concrete, offering a low-carbon alternative to traditional materials.